2016
DOI: 10.1063/1.4945783
|View full text |Cite
|
Sign up to set email alerts
|

Tuning dissociation using isoelectronically doped graphene and hexagonal boron nitride: Water and other small molecules

Abstract: Novel uses for 2-dimensional materials like graphene and hexagonal boron nitride (h-BN) are being frequently discovered especially for membrane and catalysis applications. Still however, a great deal remains to be understood about the interaction of environmentally and industrially relevant molecules such as water with these materials. Taking inspiration from advances in hybridising graphene and h-BN, we explore using density functional theory, the dissociation of water, hydrogen, methane, and methanol on grap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 89 publications
(126 reference statements)
3
23
0
Order By: Relevance
“…By using pseudopotential DFT, Jhi and Kwon found that the binding energy of H 2 for moderately substituted BN nanotubes is increased by as much as 50 % on top of carbon that substitutes boron (i.e., −8.7 vs. −13 kJ mol −1 ) . Such a potential was computationally supported in a few other works, but the prediction has not been confirmed by experimental results yet . Instead, one may cite the work reported by Portehault et al.…”
Section: Avenues For Improvementsmentioning
confidence: 88%
See 1 more Smart Citation
“…By using pseudopotential DFT, Jhi and Kwon found that the binding energy of H 2 for moderately substituted BN nanotubes is increased by as much as 50 % on top of carbon that substitutes boron (i.e., −8.7 vs. −13 kJ mol −1 ) . Such a potential was computationally supported in a few other works, but the prediction has not been confirmed by experimental results yet . Instead, one may cite the work reported by Portehault et al.…”
Section: Avenues For Improvementsmentioning
confidence: 88%
“…[36] Such ap otential was computationally supported in af ew other works, but the prediction hasn ot been confirmed by experimental resultsy et. [54][55][56][57][58] Instead, one may cite the work reported by Portehaulte tal. where nano-/mesoporousb oron carbon nitrides (e.g.,B 0.36 C 0.12 N 0.32 O 0.11 H 0.09 with a specific surface area of 1560 m 2 g À1 ,amicroporous volume of 0.64 cm 3 g À1 ,a nd am esoporousv olume of 2.23 cm 3 g À1 )r eversibly stored 1.07 wt %H 2 at À196 8Ca nd 1bar.…”
Section: Substitutional Doping Of Bnmentioning
confidence: 99%
“…This is in agreement with the patterns identified in a previous DFT study. 21 Similarly, in the configuration found for N2C, the boron atom is between two nitrogen atoms and thus forms a stronger bond with the OH fragment of water. More interestingly, the favorable configuration from B2C is less intuitive, with a boron atom that is not directly bonded to a surface atom at the active site (see Fig.…”
Section: Discussionmentioning
confidence: 86%
“…The location of the hydroxyl group at the h-BN surface occurs by attacking electrophilic born (B) sites. 9,12,[43][44][45][46][47] Experimental observations show that OH-BNNS could possess an ultra-high hydroxylation degrees. 48 In these studies, more than 88% of B atoms were hydroxylated (the proportion was obtained by XPS analysis).…”
Section: B Oh-bnns Modelsmentioning
confidence: 99%